Case series of Stargardt's disease: Our experience (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Stargardt disease is the most common form of juvenile macular degeneration. Clinically, it is characterized by pisciform flecks at lhe level of the retinal pigment epithelium and a bull's-eye maculopathy. Inheritance is usually autosomal recessive, although dominantly inherited case have been described. Both sexes are affected equally. We reported here three cases of Stargardt's macular dystrophy, who are siblings and daughters of non consanguineous parents. In case-1,2 and 3 we found the typical presentation with almost same findings.